The cloud revolution : how the convergence of new technologies will unleash the next economic boom and a roaring 2020s - Mills, Mark P. (Tantor Media, Inc., 2023)
The conventional wisdom on how technology will change the future is wrong. Mark Mills lays out a radically different and optimistic vision for what's really coming. The mainstream forecasts fall into three camps. One considers today as the "new normal," where ordering a ride or food on a smartphone or trading in bitcoins is as good as it's going to get. Another foresees a dystopian era of widespread, digitally driven job- and business-destruction. A third believes that the only technological revolution that matters will be found with renewable energy and electric cars. But according to Mills, a convergence of technologies will instead drive an economic boom over the coming decade, one that historians will characterize as the "Roaring 2020s." It will come not from any single big invention, but from the confluence of radical advances in three primary technology domains: microprocessors, materials, and machines. Accelerating and enabling all of this is the Cloud, history's biggest infrastructure. We have wrung much magic from the technologies that fueled the last long boom. And this time, we have the Cloud amplifying everything. The next long boom starts now